2006
DOI: 10.1063/1.2364600
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence tomography in turbid media based on acousto-optic modulation imaging

Abstract: The authors present a tomographic imaging technique of fluorescence in light-scattering media. Ultrasonic modulation of fluorescence based on the interaction between ultrasound and light is applied for imaging of a fluorescent material by scanning a focused sound field in which the light is modulated selectively. The on-axis sound-field characteristics that affect the light by modulating its amplitude (through variation of the refractive index and the scattering coefficient) were determined. That imaging techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 7 publications
2
95
0
Order By: Relevance
“…[8][9][10] A highly focused ultrasound beam was employed to modulate fluorophores. [8][9][10][11] The UMF signal can be detected and used to quantify the fluorophore information in the small ultrasound focal volume. Thus, a fluorescence image with ultrasound resolution can be achieved at a large depth.…”
mentioning
confidence: 99%
“…[8][9][10] A highly focused ultrasound beam was employed to modulate fluorophores. [8][9][10][11] The UMF signal can be detected and used to quantify the fluorophore information in the small ultrasound focal volume. Thus, a fluorescence image with ultrasound resolution can be achieved at a large depth.…”
mentioning
confidence: 99%
“…10 For example, acoustooptic modulation of fluorescence has been applied to imaging in turbid media. 11,12 Optically modulated fluorescence signals were obtained from organic fluorophores and fluorescent proteins making use of photoisomerization reactions 13,14 and from DNA-encapsulated Ag clusters via the excitation of dark states with near-infrared light. 15 The emission of FRET pairs can be modulated optically by depleting the ground state of the acceptor 16 or quenching its emission.…”
mentioning
confidence: 99%
“…However Krishnan [29] proposed a theory that fluorescent light is modulated by the gradient of the refractive index by an acoustic lens effect (6). Kobayashi et al [30] showed the feasibility of detecting this modulated intensity in fluorescence. (3), variation of the position of scattering particles (4), scattering particle cross section variation (5) and variation in refractive index leading to Bragg diffraction patterns (6).…”
Section: Acousto-optic Tagging Mechanismsmentioning
confidence: 99%
“…Efforts similar to DOT have to be made to perform optical tomography with fluorescent light [83]. Kobayashi et al [30] Hall et al [84] and Yuan et al [83,[85][86][87][88] investigated techniques to modulate, and thereby localize, this fluorescent light in turbid media.…”
Section: Acousto-optic-modulated-fluorescence--mentioning
confidence: 99%
See 1 more Smart Citation